Pregled sodne prakse s področja varovanja osebnih podatkov, zaupnosti, poslovne skrivnosti - Šetinc Tekavc, Martina (Delavci in delodajalci, 2018)
Performance of work tasks and payment are essential components of employment relationship arising from a contract of employment, but they are by no means the only ones. On the side of workers, obligations arising from the prohibition of causing damage to the employer or the requirement of loyalty to the employer are also important. The article deals with possible violations of the obligation of personal data protection, confidentiality, protection of business secrets and competing with the employer. In assessing the lawfulness of termination of the employment contract or the existence of damages and eventual disciplinary liability, the courts determine the nature of the data, the existence of violations and possible reservations that render the sanction imposed inappropriate (eg. interference with freedom of expression).
Keywords: competitive ban and clause; confidentiality; delovnopravne sankcije; konkurenčna prepoved in klavzula; labor law measures; lojalnost do delodajalca; loyalty to the employer; personal data protection; protection of business secrets; varovanje poslovne skrivnosti; varstvo osebnih podatkov; zaupnost